Preventing Foodborne Illness: Salmonellosis - Keith R. Schneider; Renée M. Goodrich; Sarah Z. Waithe (EDIS)
This is one in a series of fact sheets targeting the processing and retail sector of food science. This document is FSHN0214, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida. Publication: January 2003.